ECUMICT 2014 Proceedings of the European Conference on the Use of Modern Information and Communication Technologies, Gent, March 2014 - Strycker, Lieven De.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This proceeding present the outcome of the 6th. European Conference on the Use of Modern Information and Communication Technologies. The ECUMICT 2014 was hold in Gent in March 2014 and presented recent research, that has a close relationship with practical implementation of Security for mobile communications and data access Interface technology for mobile devices Application development for mobile devices Positioning and localization, asset tracking and tracing Design and applications of RFID systems Developments in the framework of IoT and M2M communications Design and applications of WSNs Embedded programming for WSNs New developments and applications of WPAN/WLAN standards Mobile multimedia systems Wireless telecommunication networks and mobile services Optimization techniques in wireless networks Developments in ad-hoc and mesh networks Applications of digital signal processing for mobile applications Applications of MEMs in WSNs.
Keywords: Engineering; Electrical engineering; Engineering; Communications Engineering, Networks; Information Systems Applications (incl. Internet).; Signal, Image and Speech Processing; Electronic books